TRANSFORMATION EFFECTS OF BASIC-MOTOR ABILITIES OF FOOTBALL PLAYERS 12 TO 14 YEARS OF AGE - Alen Kapidžić; Harun Ismaili; Jasmin Bilalić; Dragoljub Bekvalac (Sport Scientific And Practical Aspects, 2025)
The main purpose of the research is to determine whether the working program containing large number of specific exercises will contribute to higher dynamic growth among the experimental group participants comparing to the control group participants according to the variables for evaluation of basic-motor abilities. In order to evaluate basic-motor abilities of testing candidates a battery with 15 measuring instruments was used. The research testing group is consisted of 78 football players 12 to 14 years of age, members of soccer schools in football clubs “SLOBODA”, “TUZLA” and “KLUB – 7” all from Tuzla. Attendees of all three soccer schools are members of pioneer competition selection within the football clubs they belong to. In order to reach purpose of the research, certain mathematical-statistical procedure has been used. Multivariate analysis of covariance was used in order to determine the effects, i.e. whether the experimental group expressed statistically significant effects after the program had been implemented comparing to the control group. Based on the results reached by Multivariate analysis of covariance, it has been determined that the experimental group achieved higher dynamic growth in four out of fifteen variables for evaluation of basic-motor abilities, including: MBFTAR – hand tapping, MFLBOS – side splits, MAGTUP – zig-zag test (running in the rectangular), MBAP2Z – both legs stand transversally on the bench with eyes closed. We have to emphasize that the working program containing both specific and acyclic exercises lead to statistically significant effects in the above mentioned variables. These data can contribute to more efficient selection of training means which would be applied in the work with football players of younger age groups.